Time-trends and correlates of obesity in Czech adolescents in relation to family socioeconomic status over a 16-year study period (2002-2018) - Sigmund, Erik; Sigmundová, Dagmar; Badura, Petr; Voráčová, Jaroslava; Vladimír, Hobza; Hollein, Tomáš; Pavelka, Jan; Půžová, Zuzana; Kalman, Michal (BMC public health, 2020)
BACKGROUND: The main objective of the study is to analyse the changes in the prevalence of obesity among Czech adolescents between 2002 and 2018 with regard to the socioeconomic status (SES) of adolescents' families and to find SES-separated correlates of adolescents' obesity in 2018. METHODS: A nationally representative sample of 29,879 adolescents (49.6% of them boys) aged 10.5-16.5 years was drawn from the Health Behaviour in School-aged Children cross-sectional, self-reported questionnaire surveys conducted in 2002, 2006, 2010, 2014, and 2018 in Czechia. Chi-square (χ2) tests were performed to assess the changes in the prevalence of obesity in both genders and all SES categories of adolescents between 2002 and 2018, and SES category-related differences in the prevalence of obesity in 2018 separately for boys and girls. A series of multiple stepwise logistic regression (backward elimination) analyses were used to reveal obesity correlates separately for SES categories of adolescents. RESULTS: Across the quadrennial surveys from 2002 to 2018, we observed a clear increase in the prevalence of obesity in all SES categories of adolescents, which was most striking (p < 0.05) in adolescents with low SES (boys: + 7.5% points (p.p.); girls + 2.4 p.p.). When all the survey cycles were compared, the highest prevalence of obesity was evident in the low-SES adolescents in 2018, both in girls (5.1%) and boys (12.0%). Regardless of the adolescent SES category, the lower odds of obesity were significantly (p < 0.05) associated with regular vigorous physical activity (PA), participation in organized sport, and daily consumption of sweets. In addition, at least 60 min of moderate-to-vigorous PA significantly reduced the odds of obesity in adolescents of low and high SES categories. CONCLUSIONS: An unreasonable increase in the prevalence of obesity in adolescents with low SES highlights the need to prevent obesity in adolescents with a low-SES background. Additionally, significantly higher odds of obesity in 11- and 13-year-old adolescents from low-SES families, compared with their peers aged 15, indicated an expectable rise in obesity in older low-SES adolescents in the near future.
Keywords: Surveys and Questionnaires; Humans; dítě; prevalence; Child; Pediatric Obesity; Female; rizikové faktory; lidé; Health Status Disparities; časové faktory; průzkumy a dotazníky; společenská třída; ženské pohlaví; obezita dětí a dospívajících; Male; Physical activity; Adolescent; Czech Republic; Cross-Sectional Studies; Prevalence; Obesity; disparity zdravotního stavu; Social Class; Health behaviour of school-aged children study; Česká republika; mužské pohlaví; Socioeconomic status; Time Factors; průřezové studie; mladiství; Risk Factors